Performance art is an effective site for the exploration of a feminist discourse, the female psyche, and an explosive space in which to challenge the status quo - Sarkin, Daniella (My University, 2014)
This research report proposes that Performance Art is an effective site for the exploration of feminist discourse and the female psyche, and an explosive space in which to challenge the status quo. This paper uses the Performance Art piece Naked on a Goat, choreographed by Robin Orlin, to illustrate and examine this proposition. Performance Art as a genre allows female Performance Artists the space to explore an alternate discourse to that of mainstream culture. It is here that female artists are able to express and confront their experiences, emotions and concepts with regard to being "woman". This in turn then gives the space to challenge specific issues within the status quo, whilst exploring their own discourse. In this introduction: • I will explore a definition for the medium Performana* Art • I will explain why Robin Oriin's Naked on a Goat is used to examine the above proposition. • I will suggest how Naked on a Goat positions a feminist discourse with a racial one in the context of South Africa today. I will examine how the work broaches psychological themes that are particular to the female psyche (in situations of inequality and domination).